Factors Influencing E-Hailing Service Use among Universiti Tun Hussein Onn Malaysia (UTHM), Faculty of Technology Management and Business (FPTP) Students - Arumugam, Surendran; Ismail, Fadillah (Research in Management of Technology and Business, 2026)
E-hailing services have become an increasingly popular mode of transportation among university students in Malaysia, particularly for daily commuting. Despite their widespread use, factors influencing students’ adoption of these services remain underexplored. This study aims to examine the effects of perceived usefulness, perceived ease of use, fare pricing, and safety concerns on the intention to use e-hailing services among undergraduate students at Universiti Tun Hussein Onn Malaysia (UTHM), focusing on the Faculty of Technology Management and Business (FPTP). Guided by the Technology Acceptance Model (TAM), a quantitative research design was employed, with data collected from 313 students selected through stratified random sampling. A structured questionnaire adapted from established TAM studies and validated by two experts, followed by a pilot test of 20 respondents, was used to ensure reliability and content validity. The reliability analysis indicated excellent internal consistency (Cronbach’s alpha = 0.909). Statistical analysis using SPSS version 26, including descriptive statistics and Pearson correlation, revealed that perceived usefulness and ease of use significantly influence students’ intention to use e-hailing services. Fare pricing and safety concerns also have meaningful effects, with a moderate negative correlation observed between fare perceptions and usage (r = −0.412, n = 240, p = 0.001). The findings suggest that improving app functionality, implementing enhanced safety measures, and maintaining transparent pricing could increase adoption among students. Practically, the study offers insights for e-hailing service providers to develop reliable, user-friendly, and safe platforms with fair pricing. Academically, it contributes to the literature on technology adoption among youth, highlighting the roles of usability, safety, and cost in shaping behavioral intentions. Future research could expand to other faculties or institutions to improve generalizability.